Recent Advances in Metal–Organic Framework-Based Anticancer Hydrogels - Preeti Kush; Ranjit Singh; Parveen Kumar (Gels)
Cancer is the second leading cause of death globally and the estimated number of new cancer cases and deaths will be ∼30.2 million and 16.3 million, respectively, by 2040. These numbers cause massive, physical, emotional, and financial burdens to society and the healthcare system that lead to further research for a better and more effective therapeutic strategy to manage cancer. Metal–organic frameworks (MOFs) are promising alternative approaches for efficient drug delivery and cancer theranostics owing to their unique properties and the direct transportation of drugs into cells followed by controlled release, but they suffer from certain limitations like rigidity, poor dispersibility, fragility, aggregation probability, and limited surface accessibility. Therefore, MOFs were conjugated with polymeric hydrogels, leading to the formation of MOF-based hydrogels with abundant absorption sites, flexibility, and excellent mechanical properties. This review briefly describes the different strategies used for the synthesis and characterization of MOF-based hydrogels. Further, we place special emphasis on the recent advances in MOF-based hydrogels used to manage different cancers. Finally, we conclude the challenges and future perspectives of MOF-based hydrogels. We believe that this review will help researchers to develop more MOF-based hydrogels with augmented anticancer effects, enabling the effective management of cancer even without adverse effects.